Marathon Runners: A Fertile Market for "Green" Donations?. Issue 4 (23rd November 2021) - Triantafyllidis, Stavros; Kaplanidou, Kyriaki
Abstract: Marathon events are hosted annually by various communities around the United States. Within this context, marathon runners train and compete in various natural environments. Nature-based places can be primary training areas and often consist a large part of marathon events. Marathon runners, therefore, may care more about the quality of the nature they train in, as the environmental quality can connect to health benefits. The purpose of this study was to test how various types of marathon runner's motivations influence their environmental concern and donation intentions toward green initiatives. Data was collected from marathon runners of a marathon event using a web-survey. In total, 103 marathon runners responded fully to the questionnaire. Findings indicated motivations related to self-esteem, health benefits, and environmental concern influences significantly and positive marathon runners' donation intentions for green initiatives. Limitations are highlighted, as future research can explore further the conceptual model of this inquiry.